ANALISIS KESULITAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI PERBANDINGAN SD SWASTA ALWASHLIYAH 80 KISARAN - Anim Anim; Nur Winda Dewi; Suci Ramayanti; Maisahara Dalimunthe (Smart Education, 2025)
Abstract: This study aims to describe students' mathematical communication skills in solving comparison problems. A total of 32 sixth-grade students at AlWashliyah 80 Kisaran Private Elementary School were the subjects of this study. Data were collected by giving three essay questions focusing on comparison material. The results of the analysis showed that only a small percentage of students, namely 18.75%, had high mathematical communication skills. Another 25% were in the moderate category, while the majority of students, 56.25%, were classified as having low communication skills. Students in the high category were able to meet all the expected indicators, while students in the moderate category were only able to master two indicators. Students in the low category were generally only able to achieve one indicator. These findings confirm that mathematical communication skills play an important role in helping students understand problems and solve math questions more effectively. Keywords: Analysis; ability; mathematical communication; comparison. Abstrak: Penelitian ini bertujuan menggambarkan kemampuan komunikasi matematis siswa dalam menyelesaikan soal perbandingan. Sebanyak 32 siswa kelas VI di SD Swasta AlWashliyah 80 Kisaran menjadi subjek dalam penelitian ini. Data dikumpulkan melalui pemberian tiga soal uraian yang berfokus pada materi perbandingan. Hasil analisis menunjukkan bahwa hanya sebagian kecil siswa, yakni 18,75%, yang memiliki kemampuan komunikasi matematis pada kategori tinggi. Sebanyak 25% lainnya berada pada kategori sedang, sedangkan mayoritas siswa, yaitu 56,25%, tergolong memiliki kemampuan komunikasi yang rendah. Siswa yang termasuk kategori tinggi mampu memenuhi seluruh indikator yang diharapkan, sementara siswa yang berada pada kategori sedang hanya dapat menguasai dua indikator. Adapun siswa dengan kategori rendah umumnya hanya mampu mencapai satu indikator saja. Temuan ini menegaskan bahwa kemampuan komunikasi matematis memegang peran penting dalam membantu siswa memahami persoalan dan menyelesaikan soal matematika secara lebih efektif. Kata kunci: Analisis; kemampuan; komunikasi matematis; perbandingan.